Detailed Molecular Dynamics of the Photochromic Reaction of Spiropyran: A Semiclassical Dynamics Study. (17th June 2014) - Zhai, Gaohong; Shao, Shuai; Wu, Shaomei; Lei, Yibo; Dou, Yusheng
Abstract : A realistic semiclassical dynamics simulation study is reported for the photoinduced ring-opening reaction of spiropyran. The main simulation results show that one pathway involves hydrogen out-of-plane (HOOP) torsion of phenyl ring nearby N atom in 254 fs on the excited state and the isomerization from cis- to trans-SP that is complete in about 10 ps on the ground state after the electron transition π σ * ; the other dominate pathway corresponds to the ring-opening reaction of trans-SP to form the most stable merocyanine (MC) product. Unlike the previous theoretical finding, one C−C bond cleavage on the real molecule rather than the C−N dissociation of the model one is more probable than the ring-opening reaction after the photoexcitation of SP. The simulation findings provide more important complementarity for interpreting experimental observations, confirming the previously theoretical studies of photochromic ring-opening process and even supplying other possible reaction mechanisms.